PHYTOCHEMICAL SCREENING AND EVALUATION OF ANTIDIARRHOEAL ACTIVITY OF BUNIUM BULBOCASTANUM SEEDS EXTRACT IN EXPERIMENTAL WISTAR RATS - KHANAL, PITAMBAR; PAUDEL, NABINA; ARYAL, SUSHANT; ARYAL, PRAMOD (International Journal of Pharmacy and Pharmaceutical Sciences, 2021)
Objective: The main objective of this study was to evaluate the antidiarrheal activity of Bunim bulbocastanum seeds extracts, to exploit the medicinal use of plant in the traditional system of medicine scientifically. Methods: The adult Wistar albino rats were divided in four groups, i.e. Group M1 (control group) receiving normal saline, group M2 (test group 1) receiving the 250 mg/kg Bunium bulbocastanum extract, group M2 (test group 2) receiving the 500 mg/kg Bunium bulbocastanum extract and group M4 (reference) receiving 3 mg/kg P. O Loperamide. Each group of mice with a bodyweight of 1 ml/100 g received castor oil. Mice were sacrificed and the distance traveled by the charcoal meal and the total length of the intestine was then measured. The peristaltic index and percentage of inhibition were calculated by using the formula. Results: It was found that in the castor oil-induced intestinal transit method extract produced a significant (p<0.0001) dose-dependent reduction in the distance traveled by charcoal meal comparable to the control peak effect was at the dose of 500 mg/kg (PI=12.06±3.38). Likewise, in the diarrheal dropping test, Bunium bulbocastanum extract causes a significant (p<0.05) dose-dependent reduction in the number of wet feces i.e. the mean wet of feces was decreased from 2.3±0.44 gm to 1.28±0.36 gm i.e. significantly different from that elicited by control (0.80±0.17 gm) (p=0.0081). However, there were no significant differences in inhibition at a dose of 250 mg/kg of extract. Conclusion: This study demonstrated that the crude methanol extract from B. bulbocastanum seeds possesses significant antidiarrheal property and the presence of various secondary metabolites. This justified the antidiarrheal use of plant in the traditional system of medicine.